PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 003 SUKAJADI - Masderiani Hasibuan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this study was to improve the learning outcomes of Social Sciences fourth-grade students of Public Elementary School 003 Sukajadi with the number of students as many as 27 people, consisting of 15 male students and 12 female students. This study uses classroom action research with important stages such as planning, implementation, observation, and reflection. The results of this study show, seen from the basic score, the average value of students is 64.37, with students completing as many as 13 people or 48.14%. after the first cycle, the average value of students increased to 76.45, while students who completed it became 19 people or 70.3%. In the second cycle, the average score increased to 80.39 with students completing 23 people or 85.18%. From the results of the study, it can be concluded that the application of the inquiry learning model can improve Social Sciences learning outcomes of fourth-grade students of SD Negeri 003 Sukajadi